1999
DOI: 10.1007/bf02736925
|View full text |Cite
|
Sign up to set email alerts
|

Gangliosides and neutral glycolipids in ependymal, neuronal and primitive neuroectodermal tumors

Abstract: Neutral glycolipid and ganglioside compositions were determined on 11 ependymal tumors, 12 medulloblastomas, 6 other neuronal tumors of the brain, 4 peripheral neuroblastomas, 1 cerebral primitive neuroectodermal tumor (PNET), and 1 PNET of the thoracic wall. Within the group of tumors that can demonstrate neuronal phenotypes, there was an association between the degree of neuronal differentiation usually demonstrated by these tumors and the proportions of both GD1a and 1b-pathway gangliosides. The amount of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…The impetus for this study were our findings (Hettmer et al, 2003) and those of others (Schengrund et al, 1985;Sung et al, 1995;Yates et al, 1999), suggesting that differences in tumour tissue CbG (GD1b, GT1b and GQ1b) expression are linked to the clinical and biological behaviour of NB and other tumours. In order to obtain an in vitro model that permits a more dynamic view of NB ganglioside biosynthesis, we analysed ganglioside expression in four well-described NB cell lines, LAN-1, LAN-5, SMS-KCNR and SMS-KCN.…”
Section: Ganglioside Expression In Human Nb Cell Linessupporting
confidence: 50%
See 1 more Smart Citation
“…The impetus for this study were our findings (Hettmer et al, 2003) and those of others (Schengrund et al, 1985;Sung et al, 1995;Yates et al, 1999), suggesting that differences in tumour tissue CbG (GD1b, GT1b and GQ1b) expression are linked to the clinical and biological behaviour of NB and other tumours. In order to obtain an in vitro model that permits a more dynamic view of NB ganglioside biosynthesis, we analysed ganglioside expression in four well-described NB cell lines, LAN-1, LAN-5, SMS-KCNR and SMS-KCN.…”
Section: Ganglioside Expression In Human Nb Cell Linessupporting
confidence: 50%
“…Specifically, we previously found that among 74 human NB tumours, high (X35%) CbG expression (a) characterised nonprogressive vs progressive tumours (median 41 vs 18% of total gangliosides), and (b) was strongly predictive of a favourable outcome, even when other prognostic factors were considered (Hettmer et al, 2003). Related studies, associating low CbG levels in astrocytoma and medulloblastoma with higher histological grades and lower survival (Sung et al, 1995;Yates et al, 1999), further support the value of CbG in discriminating between different categories of malignant disease. In this context, the retinoic acid-induced increase in CbG expression in NB cells represents a transition into a ganglioside pattern which is associated with (i) neuronal differentiation in normal cells and (ii) clinically less-aggressive NB tumours, suggesting that CbGs may play a role in the biological behaviour of NB.…”
Section: Discussionmentioning
confidence: 72%
“…The most interesting and salient finding of our investigation is the increased production of endogenous IgM antibody against CaP-associated GD1a in the sera from patients with organ-confined CaP but not in sera from patients with unconfined CaP. GD1a is not CaP specific; it occurs in neural [48][49][50][51] and extraneural 3,52-56 tissue and sera 57 of patients with cancer. It is also found in normal tissue.…”
Section: Endogenous Immune Response To Gangliosidesmentioning
confidence: 71%
“…This permits further stratification of patients classified as 'good prognosis' by established markers and identifies patients at very low risk of relapse or death [6]. Studies of others, in astrocytoma and medulloblastoma, have also described an association between a progressive loss of CbG, higher histological grades, and lower survival [13][14][15].…”
mentioning
confidence: 99%